(untitled) (SCIENCE TIME JOURNAL, 2026)
Digitalization has significantly accelerated globalization in media communication. As a result, translation has become increasingly important as a key tool of intercultural communication. Media texts play a mediating role between creativity and mass communication and are characterized by strong pragmatic impact, expressive language, and deep cultural connections. In this context, preserving the author’s intention, meaning, and aesthetic value in translation becomes especially important. This task is even more complex when the author of the original text is also its translator. This article examines the methodological foundations of author’s translation in the interpretation of media texts. Modern research in translation studies and media linguistics emphasizes that author’s translation is not merely a mechanical transfer of meaning from one language to another. Instead, it is an independent creative and interpretative process. In the digital media environment, artistic perception is often influenced by market demands, which can lead to simplified meanings and reduced semantic depth in translated media texts. The article also analyzes the linguistic and extra-linguistic features of media texts that create difficulties in translation. These include their complex structure, frequent use of emotionally charged and evaluative vocabulary, stylistic inconsistency, and the implicit nature of pragmatic meaning. Special attention is given to the translation of headlines, idiomatic expressions, culturally specific elements, and stylistic devices aimed at influencing the audience. From a methodological perspective, the article highlights the importance of a holistic approach to teaching author’s translation in media studies. This approach should combine linguistic analysis, intercultural competence, pragmatic adaptation, and the effective use of modern technologies. The findings show that successful author’s translation requires more than strong language skills. It also demands an understanding of the author’s worldview, awareness of the target audience’s cultural background, and the ability to consciously recreate the pragmatic effect of the original text.